PELESTARIAN TANAMAN PURING (CODIAEUM VARIEGATUM (L.) SEBAGAI PAGAR RUMAH GADANG DI PERKAMPUNGAN ADAT NAGARI SIJUNJUNG - Armansyah Armansyah; Ronauli Fernandes Simanjuntak (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
The customary village is one of the attractions in Sijunjung district, located in Kenagarian Sijunjung, Jorong Tanah Bato, and Padang Ranah. The resilience still sees the authenticity of the traditional village of the settlement pattern with the characteristic of a house that is gonjong. This house is called Rumah Gadang (adat house). Gadang houses are generally built on the edge of the road, with oval roofs and walls with traditionally carved values. Another attraction of the big house can be seen from the yard planted with various types of croton. Croton functioned as a fence or boundary between the house and other houses. The diversity of leaf and flower colors from croton can soothe the eyes of visitors or tourists. Most croton big fence needs to be rejuvenated (replanting), because many have died, growing lush and old age. The community needs guidance and skills to be able to multiply, fertilize, and prune. This activity aims to provide information on croton diversity and its techniques for propagating, fertilizing, and pruning croton plants. This activity uses counseling methods in the form of lectures, group discussions, and demonstrations. The activity results show that the people in the Tanah Bato and Koto Ranah traditional villages have been motivated to diversify croton as a big fence. This activity concludes that the community has known croton diversity and can multiply croton cuttings that can be used as propagation material.